Availability assessment of free-space-optics links with rain data from tropical climates - Ahmed, A Basahel; Islam, Md Rafiqul; Suriza, Ahmad Zabidi; Habaebi, Mohamed Hadi (Institute of Electrical and Electronics Engineers Inc., 2017)
Rainfall in tropical environments acts as a dominant parameter for estimating the availability of free-space optics (FSO). Long fades are caused by precipitation in particular heavy rains, and this precipitation increases atmospheric attenuation due to rain and reduces the availability of optical power from FSO links. In this paper, the link availability of an FSO system is estimated under the impact of rain in a tropical climate. The influence of rain on the propagation of FSO signal is investigated based on experimental and statistical analyses of rain-rate measurements under tropical conditions. Rain-rate data are measured in Malaysia for three years and used to estimate the availability of FSO links. Models developed in Malaysia are used to predict atmospheric attenuation due to rain. Long-term statistical measurements of rain data can enable good estimation of link availability. Based on the prediction model and measured rain-rate data, the FSO link budget is analyzed, and the link availability as a function of distance is predicted. Carrier class availability limits the FSO link to a few hundred meters only, whereas enterprise class availability can exceed FSO links over a few kilometers long.